Physical properties and reactivity of pozzolans, and their influence on the properties of lime-pozzolan pastes - WALKER, ROSANNE; PAVIA, SARA (My University, 2011)
This paper studies how pozzolan properties including particle size, specific surface, chemical and mineral composition, amorphousness and water demand, affect their reactivity as well as the strength of lime?pozzolan pastes. Reactivity was evaluated with chemical, mechanical and mineralogical methods. A number of artificial pozzolans were investigated including Ground Granulated Blastfurnace Slag (GGBS); Leca; Pulverised Fuel Ash (PFA); Calcined Clay (Metastar); Microsilica (MS); Rice Husk Ash (RHA); Red Brick Dust (RBD); Tile and Yellow Brick Dust (YBD). The paper concludes that the pozzolan?s specific surface has a much greater influence on the water demand of the paste than its particle size or the lime:pozzolan ratio. It was evidenced that each pozzolan has a particular water demand for a given workability that increased with its specific surface; and that the replacement of lime by pozzolan lowers the water demand of the paste except for Metastar, on account of its greater fineness and specific surface. There is a good correlation between the chemical and physical activity indices and the rate of portlandite consumption. These evidenced that the most amorphous pozzolans (Metastar, GGBS, RHA and MS) are the most active. Finally, it also appears from the results, that the amount of lime combined by reactive crystalline phases in the pozzolans is insignificant when compared to that bound by their amorphous fraction. The paper concludes that amorphousness determines pozzolan reactivity to a much greater extent than any other pozzolan property. It also concludes that the specific surface area of the pozzolan governs the water demand of the paste, while amorphousness largely determines the strength of the paste. In contrast, the chemical composition of the pozzolan is not instrumental as a variable affecting neither pozzolan reactivity nor the strength of the paste.
PUBLISHED
Keywords: Construction engineering; Pozzolan; Amorphousness; Specific surface; Nanoscience & Materials